2021
DOI: 10.22541/au.162605830.04721325/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 and vertical transmission: assessing the expression of ACE2 / TMPRSS2 in the human fetus and placenta to assess the risk of SARS-CoV-2 infection.

Abstract: Background: While pregnant women have been identified as a potentially at-risk group concerning COVID-19 infection, little is known regarding the susceptibility of the fetus to infection. Co-expression of ACE2 and TMPRSS2 has been identified as a pre-requisite for infection, and expression across different tissues is known to vary between children and adults. However, the expression of these proteins in the fetus is unknown. Methods: We performed a retrospective analysis of single cell data repositories. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…This could be on account of the placentas included in Taglauer et al (18) study consist of a placenta cohort from the third trimester COVID-19 positive pregnancies. The finding of decreasing ACE2 receptors at the third trimester is consistent with other eligible studies found in our search (19,20). This might suggest that SARS-CoV-2 -placenta infection might have an alternative route, or placenta at term provides a remarkable protective role in developing fetus against SARS-CoV-2 infection.…”
Section: Literature Review Of What Is Known Based On Eligible Studiessupporting
confidence: 91%
See 4 more Smart Citations
“…This could be on account of the placentas included in Taglauer et al (18) study consist of a placenta cohort from the third trimester COVID-19 positive pregnancies. The finding of decreasing ACE2 receptors at the third trimester is consistent with other eligible studies found in our search (19,20). This might suggest that SARS-CoV-2 -placenta infection might have an alternative route, or placenta at term provides a remarkable protective role in developing fetus against SARS-CoV-2 infection.…”
Section: Literature Review Of What Is Known Based On Eligible Studiessupporting
confidence: 91%
“…Therefore, this path might be rare as well. Furthermore, there was no evidence of ACE2 and TMPRSS2 proteins co-expression in the placenta in the second trimester to term (20). The lack of evidence for ACE2 and TMPRSS2 co-expression in singlecell and single-nuclei transcriptomic analysis in these studies indicates a low likelihood of placenta infection and vertical transmission at term.…”
Section: Literature Review Of What Is Known Based On Eligible Studiesmentioning
confidence: 58%
See 3 more Smart Citations